Development of Krabok (Irvingia malayana) wax as a suppository base - P. Sirisa-Ard (2018)
Krabok (Irvingia malayana) wax was modified to obtain elasticity and good releasing medicament suppository bases by mixing with compounds such as vegetable oils, mineral oil, fatty acids and semi-synthetic waxes in various proportions to produce bases with melting range of 33-37°C. Compounds which passed the screening tests including rice bran oil, mineral oil (heavy), Span 20, cotton seed oil and polyethylene glycol (PEG) 40 stearate were combined with wax and prepared as suppositories. Drug released study demonstrated that wax with 15% cotton seed oil and 15% PEG 40 stearate was the best in releasing diclofenac into the medium. All wax mixtures become harder after three months storage together with darker color and white surface coating. Moreover, wax mixed with oleic acid gave the lowest onset temperature of melting point. From all information obtained, 11 formulae were prepared and tested for their suitability as systemic suppository bases. Only 3 formulae were chosen and re-prepared with the addition of 5% diclofenac sodium. All formulae were too soft ( < 600 g) when compared to Witepsol W35. Formula 9, containing 70% wax, 15% cotton seed oil and 15% oleic acid, was the slowest to disintegrate which was due to the absence of surfactant in its formula. However, formula 9 released twice the amount of diclofenac into the medium when compared to that of Witepsol W35 and Formula 7 gave similar drug released pattern as that of Witepsol W35. Suggestion for further study is to improve the hardness of the base to 2-3 kg to withstand the break forces caused by various types of handlings i.e. production, packaging, shipping and patient in-use. © ISHS.